Unidirectional and bidirectional flow in a narrow corridor with body rotation - Yanagisawa, Daichi; Feliciani, Claudio; Nishinari, Katsuhiro (Collective Dynamics, 2020)
In this paper, we developed a new pedestrian model, where pedestrians are represented with three circles and rotate their body to avoid others. In most pedestrian models, the body posture of pedestrians is statically connected with the walking direction; however, they may become different in our model, in other words, pedestrians can walk sideways. We conducted simulation on bidirectional flow in a narrow corridor where body rotation is necessary to avoid collisions and succeeded to reproduce realistic fundamental diagram.